Psychological and pedagogical management of development and self-development of the student’s personality in the conditions of school of vital creativity - Рева, Ю. В. (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the problem of psychological and pedagogical guidance by development and self-development of a pupil’s personality from the positions of school of life creativity.